1067. Comparative Effectiveness of Nafcillin or Oxacillin, Cefazolin, and Piperacillin/Tazobactam in Methicillin-Sensitive Staphylococcus aureus Bacteremia. (26th November 2018) - Beganovic, Maya; Cusumano, Jaclyn; Lopes, Vrishali; LaPlante, Kerry; Caffrey, Aisling
Abstract: Background: β-Lactam antibiotics are recommended as first line for treatment of methicillin-sensitive Staphylococcus aureus (MSSA) bacteremia. The objective of this study was to compare effectiveness among β-lactam therapies in MSSA bacteremia patients that were exclusively treated with one antibiotic. Methods: This was a retrospective cohort study of patients hospitalized at Veterans Affairs (VA) medical centers with MSSA bacteremia from January 1, 2002 to October 1, 2015. Patients were included if they were treated exclusively with nafcillin, oxacillin, cefazolin, or piperacillin/tazobactam (i.e., monotherapy with no changes in therapy). The primary outcome was 30-day mortality, and secondary outcomes were time to discharge, inpatient mortality, 30-day readmission, and 30-day S. aureus reinfection. Hazard ratios (HRs) and 95% confidence intervals (CI) were calculated using unadjusted, quintile adjusted, and propensity-score (PS) matched (nearest neighbor, 0.05 caliper) Cox proportional hazards regression. Results: A total of 326 patients were included in the final analysis. When comparing nafcillin ( n = 75)/oxacillin ( n = 30) with cefazolin ( n = 108), 30-day mortality was similar between groups (PS matched n = 40, HR 4.0, 95% CI 0.45–35.79), as were rates of the other outcomes assessed. When combining nafcillin/oxacillin with cefazolin, and comparing to piperacillin/tazobactam ( n = 113), 30-day mortality was significantly lower in the nafcillin/oxacillin/cefazolin group (PS matched n = 66, HR 0.29, 95% CI 0.09–0.87). Inpatient mortality and 30-day mortality were significantly lower with nafcillin/oxacillin/cefazolin in PS-adjusted analyses (HR 0.29, 95% CI 0.11–0.73 and HR 0.23, 95% CI 0.10–0.50, respectively). Conclusion: In hospitalized patients with MSSA bacteremia, no difference in mortality was observed between nafcillin/oxacillin and cefazolin in patients that were exclusively treated with these monotherapies. However, higher mortality was observed with piperacillin/tazobactam as compared with nafcillin/oxacillin/cefazolin, suggesting that it may not be as effective as other monotherapies for MSSA bacteremia. Disclosures: K. LaPlante, Merck: Grant Investigator, Research grant. Pfizer Pharmaceuticals: Grant Investigator, Research grant. Allergan: Scientific Advisor, Honorarium. Ocean Spray Cranberries, Inc.: Grant Investigator and Scientific Advisor, Honorarium and Research grant. Achaogen, Inc.: Scientific Advisor, Honorarium. Zavante Therapeutics, Inc.: Scientific Advisor, Honorarium. A. Caffrey, Merck: Grant Investigator, Research grant. The Medicine's Company: Grant Investigator, Research grant. Pfizer: Grant Investigator, Research grant.